Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 106752441 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Specimen", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present" ] } The dataset includes 106752441 records from 13125 constituent datasets: 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 6 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 138 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 20520 records from University of Guam Insect Collection. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 570 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 2516 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1189 records from UWIZM Molluscs. 4083 records from MCP-Aves - Coleção de Aves. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 625 records from Mycology collection, Norwegian Forest and Landscape Institute. 206 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 274611 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 523 records from Herbarium of the Institute of the problems of Northern development (TMN). 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 88 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 26 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 7283 records from Colecção Entomológica IIA. 1070 records from DMNS Egg Collection (Arctos). 853 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 987 records from Orthoptera - SMF. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1702 records from BioGIS - Bryophytes - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 45970 records from Herbarium Universitatis Daugavpiliensis. 592 records from Colección de Entomología - Curculionidae. 748 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 6 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 2 records from Megaluropidae *. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 16519 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6230 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 981 records from Bees in the UVM Zadock Thompson Zoological Collection. 14 records from NZCS Brownsberg Nature Park Monitoring. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2 records from Description of a new species of Cosmocerca Diesing, 1861 (Nematoda Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae from Asansol coal-field area, West Bengal, India. 39 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 192 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 10000 records from 2020_biodiversity_information_specimen. 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 13 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 104152 records from The Himalayan Uplands Plant database (HUP Version 1). 1315 records from National Museum of Natural Science. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 5 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 232 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 115 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 6 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 9883 records from University of Nebraska State Museum Birds Collection. 30348 records from University of California Santa Barbara Invertebrate Zoology Collection. 2 records from Neue Milbenarten aus Kärnten. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 74426 records from Entomology Collection at the Natural History Museum of Utah. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 137 records from Hartland Nature Club Lepidoptera Collection. 86314 records from ALCB - Herbário Alexandre Leal Costa. 9 records from Herbarium specimens of Limoges university (LIMO). 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 89875 records from Fish specimens of Kagoshima University Museum. 3825 records from UTEP Invertebrates (Arctos). 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 10 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 7 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 661 records from Flora útil del Municipio de la Huerta, Jalisco. 1955 records from SIM-Fungal records compiled by Joan Montón. 747015 records from Western Australian Museum provider for OZCAM. 3934 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 445 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 839 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 11 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 23 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 101 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 212309 records from University of Minnesota Insect Collection. 135311 records from ARABEL - Arachnologia Belgica. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 174 records from Antarctic pycnogonids. 60962 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 385 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 66051 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 46 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 173 records from UWIZM Anoles. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Reptilia ZMK. 1290 records from Diversity of Spiders from Azorean Trails. 1 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10283 records from Inventario de Hymenóptera; parasítica en México. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 5 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 82 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 414 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 678 records from Lucanidae. 29 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 41 records from MSUM Ichthyology and Herpetology Collections. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 4 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 22 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 7600 records from ERBG AVH data. 4 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 61174 records from Tiroler Landesmuseum Ferdinandeum. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 87 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 8 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 286 records from California State University, Long Beach Birds. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 141 records from Collection Hydrozoa - ZSM München. 1 records from Astragalus orientopersicus, sp. nov. (Fabaceae), a new taxon from the Khorassan province (Iran). 3588 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 270 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 2 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 7 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 57 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 4 records from Herbarium Senckenbergianum (FR) - Protista. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 2 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 197 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 203 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 188266 records from Allan Herbarium (CHR). 68535 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 14232 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 16 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 1124 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 1 records from MVZ Herp Observations (Arctos). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 3 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 7383 records from Marie-Victorin Herbarium (MT) - Bryophytes. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 20 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 3143 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 753 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 92380 records from CAS Entomology (ENT). 6048 records from Naturalis Biodiversity Center (NL) - Pisces. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1149 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 267172 records from hymenoptera. 1618 records from Naturalis Biodiversity Center (NL) - Crustacea. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 21 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 25 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 1594 records from The Broward College Insect Collection. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 3 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 1 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 1 records from Phliantidae *. 53207 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 22 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 2875 records from Weber State University Herbarium. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 553 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 320 records from Myxomycetes collection of the University of Eastern Finland. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 11 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 32 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 17 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 137028 records from Arizona State University Hasbrouck Insect Collection. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2274 records from Lista florística de la Costa Grande del estado de Guerrero. 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 179 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 40 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 11 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 11994 records from Hatikka Observation Database. 2531 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 298 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5502 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Mycetocharina (Alleculopsis) bahukalatensis sp. nov. (Coleoptera: Tenebrionidae: Alleculinae) from Iran. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 5 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 19535 records from Eden Arthropod Azores Database. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 27 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2081 records from Thrips (Thysanoptera) in Norway. 1 records from A new species of Homo from the Late Pleistocene of the Philippines. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 4 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 1 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 26 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1763 records from Arachnida of Costa Rica (INBio). 2 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 188 records from Occurrence of some antimalarial plants from Cameroon. 2 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 3 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 24 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 1 records from Niuailan, a new genus to accommodate Carneoryctes peterseni (Endrődi, 1967) (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from New Ireland, Papua New Guinea. 228 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 25 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 11 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 1 records from Melphidippidae *. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 11837 records from NCSM Non-molluscan Invertebrates Collection. 106407 records from The AAU Herbarium Database. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 2 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 913 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 7403 records from Colecção Entomológica do Museu de História Natural de Maputo. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 403 records from Collection Polychaeta - ZSRO. 41661 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 14 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 93 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 22 records from New species of black corals (Cnidaria: Anthozoa: Antipatharia) from deep- sea seamounts and ridges in the North Pacific. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1212 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1696 records from Herbier National de Guinée (HNG). 25 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4479 records from Iowa State University Fishes Collection. 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 300 records from EDIT - ATBI in Gemer area (Slovakia). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 69 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 11321 records from WOLL AVH data. 1394 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 20004 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 865 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 2344 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 647 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 13 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8114 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 670 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6661 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1 records from Description of a new whiteflyı Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ı infesting Quercus leucotrichophora (Fagaceae) in the Western Himalayaı India. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 9 records from A new species of Anchoviella Fowler, 1911 (Clupeiformes: Engraulidae) from the Amazon basin, Brazil. 198 records from Ixias butterfly specimens at Museum Zoologi Bogor, Indonesia. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 4 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 27 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 4545 records from Gunma Museum of Natural History, Fungi Specimen. 33235 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 11128 records from Pteridophyte of the Urals and adjacent areas. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 11 records from Qarshi Botanical Garden. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 5 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 8 records from Cryptic new species of Nesoecia Scudder, 1893 (Orthoptera: Tettigoniidae Pseudophyllinae) from northeastern, Mexico. 1662 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 160952 records from UWFC Ichthyology Collection. 3 records from A revision of pipistrelle-like bats (Mammalia: Chiroptera: Vespertilionidae) in East Africa with the description of new genera and species. 1811 records from Mycological Collection of Osaka Museum of Natural History. 6910 records from Auburn University Museum of Natural History Invertebrates. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 27 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 26 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from Notes on Allium section Rhizirideum (Amaryllidaceae) in South Korea and northeastern China: with a new species from Ulleungdo Island. 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 17204 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 80300 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6922 records from MUST, Insecta. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 2 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 72012 records from University of Tennessee Fungal Herbarium. 79368 records from University of Michigan Museum of Zoology, Division of Mollusks. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 2519 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 2103 records from Flora ficológica de la huasteca potosina. 3768 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 96 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 2 records from Integrative taxonomy reveals a new but common Neotropical treefrog, hidden under the name Boana xerophylla. 11 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 9 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 1 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 2 records from A new species of Minooa Yamanaka, 1996 (Lepidoptera, Pyralidae) from Xizang China. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 2 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 292275 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 7 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 3 records from Description of Ghatiana, a new genus of freshwater crab, with two new species and a new species of Gubernatoriana (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from the Western Ghat Mountains, India. 9 records from New occurrences for the flora of Mount Lebanon and rediscovery of Daphne pontica. 165 records from Tetrápodos de Uruguay. 34 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 4 records from Schistura thavonei, a new species of loach from northwestern Laos (Teleostei: Nemacheilidae). 200 records from 2019_nsmk_mm_20200324. 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 15120 records from University of Kentucky Insect Collection. 7 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 20613 records from UAM Bird Collection (Arctos). 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 1 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 2098 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 13 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 73 records from Swedish Malaise Trap Project (SMTP) - small Sciaroidea families. 51 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 4 records from Descriptionoftwonew speciesofDinetus Panzer, 1806 (Hymenoptera: Crabronidae Dinetinae) with key to species. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 18 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 818 records from The Golden wasps collection (Chrysididae) at the Staatliches Museum für Naturkunde Stuttgart. 326 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 6057 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 69 records from Montana State University - Billings. 70 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 226053 records from Oskarshamn herbarium (OHN). 1 records from First record of Petrobia (Petrobia) pseudotetranychina (Trombidiformes: Tetranychidae) in Asia, with two new host plants for Tetranychidae from Iran. 127 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 12536 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica Tapachula). 1 records from A new epigean species of the genus Anelpistina (Insecta: Zygentoma: Nicoletiidae) from Sierra de El Abra, Taninul, Mexico. 5 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 678 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 173 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 95 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 2903 records from Algae collection, Oslo (O) UiO. 72 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 11 records from Diversity of intertidal, epibiotic, and fouling barnacles (Cirripedia, Thoracica) from Gujarat, northwest India. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 7083 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 952 records from Guinea-Bissau Herpetological Collection - IICT. 9 records from A new species and new records of minuta - group Gnamptogenys from Brazil (Hymenoptera: Formicidae). 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 1873 records from Global Distribution and Diversity of Solenidae Species. 869 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 3 records from Studies On Korean Stoneflies (Insecta: Plecoptera) With Descriptions Of Two New Species. 2 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 39 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 158 records from Studies On The Plecoptera Of The Kootenay Lake Drainage: A Revisitation Of The Stoneflies From The Purcell Range, British Columbia, Canada. 22 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 1 records from On the rare Neotropical genus Ophionthus Bernhauer (Coleoptera: Staphylinidae: Staphylininae): redescription of the type species and description of a new species. 1110 records from Insect (Lepidoptera) Biodiversity Across Forest Canopy and Understorey in SE-Asia BIFA5_026. 50 records from Marine algal (seaweed) flora of Terceira Island, Azores. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 9 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 2 records from Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis). 18539 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1750 records from Colección del Herbario de la Universidad de los Llanos. 2 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 6755 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 318 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 598 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 6977 records from 2019_NSMK_PL_2. 6241 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 15183 records from Collection Pisces SMF. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 67 records from MEXU/Tipos de plantas vasculares. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 14302 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 19 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 434 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 52 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 11686 records from NCSM Mammalogy Collection. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 101 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 53 records from CHAS Botany Collection (Arctos). 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 10 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 6782 records from Odonata de Veracruz. 6 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 1397 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 37 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 3662 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 11 records from Collection Ephemeroptera - SMF. 242 records from FBIP: Identification of polychaetes used as bait. 97757 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 2 records from Chalinochromis cyanophleps, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 3673 records from Spider (NSMK-SP). 4348 records from OUPR - Herbário "Professor José Badini". 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 10631 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 1 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 2 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 1872 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 3918 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 3 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 3889 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 9 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 253 records from NZCS Upper Tapanahony Expedition 1991. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 22 records from Tanzanian Vertebrate Collection. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 6 records from Anthopleura mariscali, a new species of sea anemone (Cnidaria: Anthozoa: Actiniaria) from the Galápagos Islands. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 24 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 986 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 2621 records from Fungi specimens of Saitama Museum of Natural History. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 6 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 32 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 11 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 1515 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 38846 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1942 records from Collection ornithologique A. Maës. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 46 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 51 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 4 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 11548 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 130434 records from Herbarium of Taiwan Forestry Research Institute. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 445 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 242 records from Malawi-Histeridae-Biodiversity-Data. 3700 records from Swiss National Diplopoda Databank. 9446 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 2 records from A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea Tetrigidae) from China. 1 records from A new freshwater chrysophyte, Chrysomorula cohaerens gen. et sp. nov. (Chrysophyceae, Chrysocapsaceae) from North America. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 13 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 31887 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 103 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 21 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 1933 records from Carabidae of the European North-East of Russia. 4734 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 3984 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 16 records from A revision of the genus Paraleptognathia Kudinova-Pasternak, 1981 (Crustacea: Tanaidacea) and description of four new species. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 12 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 20 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 54 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 144181 records from BioFokus. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 6 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 552 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 332732 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 78 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 100 records from Brock University Herbarium (BU). 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 97 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 86 records from UWIZM Cnidarians. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1640 records from La familia Asclepiadaceae en México. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 17 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 54 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 27 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 24381 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 2 records from Glasgow Museums BRC: Chrysomelidae. 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 4 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 3277 records from USAC Mammals Collection. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 321 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 63 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 43391 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1914 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 5 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 9 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 16605 records from EAC - Herbário Prisco Bezerra. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 10902 records from Collection Crustacea - ZMB. 724 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 991 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 27 records from A contribution to the earthworm diversity (Clitellata, Moniligastridae) of Kerala, a component of the Western Ghats biodiversity hotspot, India, using integrated taxonomy. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 8 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 143 records from Dermaptera in the icipe collection. 1248 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 187 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 2048 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 4 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 6344 records from Kherson State University herbarium (KHER), Department of Botany. 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 43 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 107 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 2 records from Sideritis syriaca subsp. nusairiensis and Thymus sipyleus in Mount Lebanon. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 69 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 3 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 4 records from Two new species of Sabellariidae (Annelida, Polychaeta) from the abyss of eastern Australia. 62152 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 33 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 2162 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 5 records from The Unicorn exists! A remarkable new genus and species of Perilissini (Hymenoptera: Ichneumonidae) from South East Asia. 8 records from Hyobanche thinophila (Orobanchaceae), a new species from the Western Cape of South Africa. 28 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 68 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 6 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 1284 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 2 records from Two new freshwater species of Bacillaria (Bacillariophyta) from Dongting Lake, China. 11472 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 2 records from A new species of Togoperla (Plecoptera: Perlidae) from China with a revised key to Togoperla males. 5 records from The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species. 9 records from Two new species of the Amphinemura sinensis group (Plecoptera: Nemouridae) from southern China. 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 33 records from Bohemannia auriciliella (Nepticulidae) specimen data. 13 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 17 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 1202 records from Marine algal flora of Flores and Corvo Islands, Azores. 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 9 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 3726 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 23748 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 5 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 10 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 5 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 5 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 26380 records from JCT AVH data. 86480 records from University of Tennessee Bryophyte Herbarium. 7648 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2 records from A new species of the Goblin Spider genus Predatoroonops Brescovit, Rheims & Ott 2012 (Araneae, Dysderoidea: Oonopidae), with new records for the genus. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 31 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 5 records from Collection Myriapoda - SNSD. 14 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 6 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 71 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 8 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 5 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 396 records from MCCC - Mendocino College Coast Center Herbarium. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 1000 records from nsmk_mm_2019. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 765 records from DAR AVH data. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 2898 records from DBL_Life. 1 records from Multiple original spellings, living authors and the Code: The case of Malachius raniansis Mawlood, Hammamurad & Abdulla, 2017 (Coleoptera: Melyridae). 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 33814 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 174524 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 1615 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 436 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2988 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 36 records from University of Sindh Jamshoro Herbarium. 2 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 1254 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 3 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 2 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 14744 records from Swiss National Grasshoppers Databank. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 70427 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 35150 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 12 records from Astyanax ajuricaba: a new species from the Amazon basin in Brazil (Characiformes: Characidae). 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 1 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 1369 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 2421 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 3 records from Taxonomic revision of the genus Tarmia Lindsey, 1925 stat. rev. (Hesperiidae: Hesperiinae: Hesperiini: Moncina) with the description of a new species from the Andes. 3 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 6 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 34 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 1 records from Two atypical new species of the genus Sectonema Thorne, 1930 (Nematoda, Dorylaimida, Aporcelaimidae) from Vietnam. 4 records from Two new species of Geodiidae (Porifera, Demospongiae, Astrophorina) from the Emperor Seamounts, North Pacific Ocean. 2 records from Dima spicata Schimmel, 1999 (Elateridae: Dimini), a morphologically remarkable species endemic to China. 17 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 9 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 1584 records from Coleoptera Collection. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 73 records from Michigan Plecoptera (Stoneflies): Distribution Patterns And An Updated Species List. 231 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 1135 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 22 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 3 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 1 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 12946 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 4 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 5 records from Four New Bat Species (Rhinolophus hildebrandtii Complex) Reflect Plio-Pleistocene Divergence of Dwarfs and Giants across an Afromontane Archipelago. 1 records from Hygrotus (Coelambus) nubilus (LECONTE, 1855) on Mauna Kea (Hawaii) - first record of the genus from the Pacific zoogeographical region (Coleoptera: Dytiscidae). 1 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 5 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1 records from Toward a revision of the bamboo corals: Part 1, species in the Muricellisidinae (Octocorallia: Isididae). 2 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 8 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 120 records from Collection Crustacea ZMG. 3 records from Revision of Chinese mainland Hybovalgus Kolbe, 1904, with description of a new species, and Excisivalgus Endrödi, 1952 reduced to synonymy with Hybovalgus (Coleoptera: Scarabaeidae). 1 records from Spirlins of the southern Black Sea basin, with the description of a new species (Teleostei: Leuciscidae). 5 records from Description of two females of Leptagrion Selys (Odonata: Coenagrionidae). 1 records from Redescription of Inglisia vitrea Cockerell (Hemiptera, Coccidae) and its transfer to the genus Pseudokermes Cockerell. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México (Plantas Acuaticas Río Amacuzac). 2 records from A new genus and species of Nematalycidae (Acari: Endeostigmata). 6 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 169 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 243525 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 32 records from Vermont Records of Crayfish Worms (Branchiobdellidans) and Associated Crayfish Hosts. 44 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 314 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 81 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 5977 records from NHMO DNA Bank Vascular plants collection. 1648 records from HPL - Herbário do Jardim Botânico Plantarum. 4 records from Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species. 438 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 3 records from Scilla hakkariensis, sp. nov. (Asparagaceae: Scilloideae): a new species of Scilla L. from Hakkari (eastern Anatolia). 2466 records from TTRS Ornithology. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 5 records from Baeocera socotrana sp. nov., the first species of Scaphidiinae (Coleoptera: Staphylinidae) reported from Socotra Island. 54 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 1 records from Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands. 2 records from A new species of Dichagyris Lederer, 1857 from China (Lepidoptera, Noctuidae). 64 records from B herbarium - Botanischer Garten und Botanisches Museum Berlin-Dahlem Herbarium - Herbário Virtual REFLORA. 23 records from On Sahastata (Araneae: Filistatidae): complementary description of the generotype and two new species from Oman and Morocco. 1 records from Balanophora coralliformis (Balanophoraceae), a new species from Mt. Mingan, Luzon, Philippines. 1286 records from El género Bursera en México. Parte II. 14003 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 447 records from PSUZC-Mammal Collection. 3 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 6219 records from Canadian National Collection of Insects. 155 records from Diversity and distribution of Pleioplectron Hutton cave wētā (Orthoptera: Rhaphidophoridae: Macropathinae), with the synonymy of Weta Chopard and the description of seven new species. 1 records from Chroesthes (Acanthaceae) in Peninsular Malaysia, including a new species from Kelantan and a new record from Terengganu. 9750 records from Herbarium of University of Coimbra (COI ). 5 records from Chinese psyllids in the genus Cacopsylla (Hemiptera: Sternorrhyncha: Psylloidea) associated with Spiraea (Rosaceae). 1 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 6 records from Hyptidendron pulcherrimum Antar & Harley, sp. nov. (Hyptidinae, Lamiaceae), a new narrowly endemic species from Minas Gerais, Brazil. 1 records from New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae). 2 records from The InBIO Barcoding Initiative Database: Depressaria infernella Corley & Buchner, a new Iberian species of the Depressaria douglasella group. 2 records from A review of the powderpost beetle genera Xylothrips Lesne, 1901 and Calophagus Lesne, 1902 (Coleoptera: Bostrichidae: Bostrichinae: Xyloperthini). 1 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 10 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 1 records from Resolving the taxonomic puzzle of Boana cinerascens (Spix, 1824), with resurrection of Hyla granosa gracilis Melin, 1941 (Anura: Hylidae). 48 records from An overview of the Brazilian inselberg genus Ameroglossum (Linderniaceae, Lamiales), with the description of seven new species. 4 records from Two new species of Pristimantis (Anura: Craugastoridae) with notes on the distribution of the genus in northeastern Colombia. 7 records from Taxonomic revision of the recent marine Corbulidae (Mollusca, Bivalvia) from Brazil. 26 records from Swedish Malaise Trap Project (SMTP) - Clusiidae. 20 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 23034 records from UPCB - Herbário do Departamento de Botânica. 98 records from Taxonomic revision of the South American subgenus Canthon (Peltecanthon) Pereira, 1953 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini). 2151 records from Amphibians and Reptiles census in the Western Siberia (2002 - 2009 years of research). 2 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 10 records from A new species of Probolomyrmex from Madagascar.. 4 records from A new species of tree-hole dwelling freshwater crab of the genus Arachnothelphusa Ng, 1991 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from northern Sarawak, Malaysia, Borneo. 16 records from On the huntsman spider genera Sparianthina Banks, 1929 and Anaptomecus Simon, 1903 from South and Central America (Araneae, Sparassidae). 951 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 4 records from Lethrus (Lethrus) thracicus (Coleoptera: Geotrupidae), a new species from the European part of Turkey. 6438 records from ZFMK Coleoptera collection. 1 records from Bipolarity in sea slugs: a new species of Doridunculus (Mollusca: Nudibranchia: Onchidoridoidea) from Antarctica. 24 records from A review of Peruvian diving beetles of the genus Hydaticus Leach, 1817, with description of Hydaticus (Prodaticus) panguana sp. nov. and notes on other Neotropical species (Coleoptera: Dytiscidae). 34 records from An annotated and illustrated catalogue of the Osmylidae collection (Neuroptera) at the Natural History Museum, London. 35174 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from On some lesser known sea cucumbers in the Natural History Museum, UK (Echinodermata: Holothuroidea). 59 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 60 records from Larvae collected near deep-sea hydrothermal vent fields for microbiome study. 1 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 2 records from Scapanoclypeus hardap (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini), a new species from Hardap province, Namibia. 46 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 10 records from Kartlegging av kortdistansespredning av fremmede bartrær - Helgelandskysten. 14 records from A revision of Palaearctic and Oriental Pseudolathra. V. Two new species from Cambodia and Thailand, and additional records (Coleoptera: Staphylinidae: Paederinae). 7 records from Structural variation among species of Leeuwenia (Thysanoptera, Phlaeothripinae) with three new species from Australia. 2 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 1 records from A new species of Rhaptopetalum (Lecythidaceae) from south-western Gabon. 10 records from Two new enigmatic species of the genus Merodon Meigen (Diptera: Syrphidae) from the north-eastern Middle East. 17 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 444 records from British spiders in the collections of World Museum, National Museums Liverpool. 4 records from Two new species of Flavoperla (Plecoptera: Perlidae) from Shaanxi Province of China. 54 records from Taxonomic studies on the sac spider genus Clubiona (Araneae, Clubionidae) from Xishuangbanna Rainforest, China. 6 records from Three new species of Polana (Varpulana) (Hemiptera: Cicadellidae: Gyponini) from Brazil, with updated key to males and taxonomic notes on the female genitalia. 2 records from Ascetoaxinus quatsinoensis sp. et gen. nov. (Bivalvia: Thyasiroidea) from Vancouver Island, with notes on Conchocele Gabb, 1866, and Channelaxinus Valentich-Scott & Coan, 2012. 16 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 378 records from Tsetse flies of East Africa update. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 3680 records from Flora of Sumatra : Vascular plant collection from Batang Toru Forest deposited in ANDA Herbarium. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 2 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 2 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 433 records from pins. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 14 records from Collection Crustacea - KAUMM. 1 records from A new species of the genus Cylindratus Meng, Qin et Wang, 2020 from Northern Vietnam, with first description of 5 instar larva and a key to Vietnamese Caliscelini (Hemiptera: Fulgoromorpha: Caliscelidae). 1 records from Ceracis tzotzilicus sp. nov. (Coleoptera: Tenebrionoidea: Ciidae) from Guatemala and Mexico. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 740 records from FBIP: Baboon spider distribution records from selected South African museums. 7 records from Cavichiassus, a new genus of Hyalojassini (Hemiptera: Cicadellidae) from Brazil and first description of the genitalia of Neotrocnada rutasaca (Blocker) comb nov.. 2320 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 381 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 2 records from A new species of Parapteronemobius from Zhejiang, China (Orthoptera Trigonidiidae: Nemobiinae). 44101 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 11110 records from Royal Ontario Museum Fungarium (TRTC). 342 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 1 records from A new species of Dixonius (Squamata: Gekkonidae) from Vientiane Capital, Laos. 1 records from Scissurella nesbittae, new species, from the Gries Ranch Formation, Lewis County Washington State (Gastropoda: Vetigastropoda: Scissurellidae). 14 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 23 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 43319 records from Mammals housed at MHNG, Geneva. 2 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 2630 records from Swiss Psyllid (Hemiptera) Collections - Basel. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 4 records from Two new species of the genus Bolboceras Kirby, 1819 (Coleoptera: Bolboceratidae Bolboceratinae) from India with an updated identification key of the Bolboceras nigricans Westwood, 1848 species group. 16 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 8 records from Notes on the taxonomy of Potamonautes obesus (A Milne-Edwards, 1868) and Potamonautes calcaratus (Gordon, 1929) (Brachyura: Potamoidea: Potamonautidae) from eastern and southern Africa. 225 records from UWIZM Mantodea. 1 records from A new and five rare bdelloids from Korea. 430 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 3 records from Studies on Neotropical crickets: The continental Otteiini taxa (Orthoptera Phalangopsidae), those cave crickets are not confined to the West Indies. 6 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 450 records from 2020_nsmk_smpl_pl. 1 records from Taxonomic study of Hoplias microlepis (Günther, 1864), a trans-Andean species of trahiras (Ostariophysi: Characiformes: Erythrinidae). 388 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 9 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 9 records from Small, uniform, and rarely collected-an integrated taxonomic revision of Afromicracis bark beetles (Coleoptera, Scolytinae). 2 records from New and interesting species of the generaGalumna andPergalumna (Acari, Oribatida, Galumnidae) from the Montagne d’Ambre National Park, Madagascar. 22 records from New records of ant species from Yunnan, China. 22 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 1824 records from Caracterización biológica en la Serranía de San Lucas 2015. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 1065 records from Bird specimens of Komatsu City Museum. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 51 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 40 records from Cephalocyclus iohannisgabrielis (Coleoptera: Scarabaeidae: Aphodiinae), a new species from Oaxaca, Mexico. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 6 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 14 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 19761 records from NEON Biorepository Invertebrate Bycatch Collection (Archive Pooling). 80 records from Collection Crustacea - ZSRO. 7 records from Sponge fauna of the New Siberian Shoal: biodiversity and some features of formation. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Sinaloa_2008). 2 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Pakistan. 1 records from Anemone pindariensis sp. nov., a new species from Pindari valley of the Western Himalaya, India. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 5 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 5 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 6 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 3 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 423 records from Collembola of the Chernaya river basin. 7 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 22327 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 274 records from New apinnate Prionospio (Annelida: Spionidae) species from southeastern Brazil. 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 391 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 31 records from Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae). 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 9646 records from University of Nebraska State Museum Fish Collection. 102 records from Colección de Zoología Invertebrados - Helmintología. 2 records from A new species of the “ apacheanus ” group of genus Pseudouroctonus from western Texas (Scorpiones: Vaejovidae). 11965 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 92 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 27509 records from Fishes of INEP and NFH collections. 220579 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 254 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 4 records from Polyzosteria cockroaches in Tasmania (Blattodea: Blattidae: Polyzosteriinae) represent a new, endemic species, with allopatric alpine and coastal sub-populations. 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 50 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 56 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 5 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 1 records from Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae). 1 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 451 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 1470 records from Swedish Malaise Trap Project (SMTP) - Coleoptera. 3 records from On the taxonomic position of Phaenomenella Fraussen & Hadorn, 2006 (Neogastropoda, Buccinoidea) with description of two new species. 2 records from Glyptothorax chimtuipuiensis, a new species of catfish (Teleostei: Sisoridae) from the Koladyne basin, India. 4 records from A new lacewing species of the Chrysoperla carnea species-group from central Asia associated with conifers (Neuroptera: Chrysopidae). 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 7 records from Voragocoris weirauchae sp. n. (Heteroptera: Schizopteridae: Schizopterinae), a further minute litter bug species from Brazil. 5 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 143983 records from NINA insect database. 5 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 3 records from A new spider species of the genus Sudharmia from Sumatra, Indonesia (Araneae, Liocranidae). 17 records from Review of the subtribe Gyrophaenina Kraatz 1856 (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) of Middle Asia, with emphasis on the fauna of Kazakhstan. 2 records from Chaenothecopsis neocaledonica sp. nov.: The first resinicolous mycocalicioid fungus from an araucarian conifer. 2 records from Brachiopods from Late Jurassic-Early Cretaceous hydrocarbon seep deposits, central Spitsbergen, Svalbard. 8 records from Five new species of Homalotylus Mayr (Hymenoptera: Encyrtidae) - from India with a key to Indian species. 100 records from orstom_macassar_corindon_1980. 39635 records from Lichen herbarium TRH, NTNU University Museum. 17 records from Diversity of the longhorned beetles (Coleoptera: Cerambycidae) from Cuatro Ciénegas Basin, Coahuila, Mexico. 2 records from Ceropsylla pouteriae Burckhardt sp. nov. (Hemiptera: Psylloidea: Triozidae) ı a new species of jumping plant-louse inducing galls on the leaves of Pouteria ramiflora (Mart.) Radlk. (Sapotaceae): taxonomyı gall structure and histochemistry. 2 records from First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India. 41 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 25 records from Révision des Higonius Lewis, 1883, et genres apparentés (Insecta, Coleoptera, Brentidae). 1475 records from Collembola of forested tundra in Vorkuta surroundings (1978-1979 and 1985). 8 records from Triplectides Kolenati (Trichoptera: Leptoceridae) from Brazil: A new species, new records and an identification key. 85 records from A revision of the endemic South African long-jawed ground spider genus Drassodella Hewitt, 1916 (Araneae: Gallieniellidae). 428 records from Swedish Malaise Trap Project (SMTP) - Auchenorrhyncha excl Delphacidae. 31 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 84 records from Ejemplares de Cortinarius Colectados por Camile Truong depositados en CORD. 2034 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 3 records from Five new species of Enchytraeidae (Annelida: Clitellata) from Mediterranean woodlands of Italy and reaffirmed validity of Achaeta etrusca, Fridericia bulbosa and F. miraflores. 5619 records from Plant species occurrence in the upper to mid Tana River Basin based on specimen records at the East African Herbarium (EA), Nairobi, Kenya. 3076 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 1 records from Crenicichla ploegi, a new species of pike-cichlid of the C. saxatilis group from the Rio Juruena and upper Rio Paraguai basins in Brazil, with an updated diagnosis and biogeographical comments on the group (Teleostei: Cichlidae). 13 records from A review of the hyperiidean amphipod superfamily Vibilioidea Bowman and Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea). 2 records from Discovery of the genus Dioedus LeConte, 1862 from China, with description of a new species (Coleoptera: Tenebrionidae). 3 records from Comparative phylogeography of bamboo bats of the genus Tylonycteris (Chiroptera, Vespertilionidae) in Southeast Asia. 495 records from Usac, Cecon, Herbario USCG. 1 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 12 records from A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from the middle rio São Francisco and upper and middle rio Tocantins basins, Brazil, with comments on its biogeographic history. 5 records from New genus of the subfamily Oscinellinae from Brazil (Diptera: Chloropidae). 6424 records from Base de datos de las pteridofitas del estado de Veracruz, México. 56 records from Two new species and new records of the genus Astenus from Madagascar (Coleoptera: Staphylinidae: Paederinae). 1 records from A contribution to the Mutillidae (Hymenoptera) of Hong Kong. 2 records from Heizmannia rajagopalani n. sp. (Diptera: Culicidae) in Kerala, India, a species previously misidentified as Hz. metallica (Leicester). 9956 records from ZFMK Orthopteroidea collection. 16 records from Revision of Korean species of the genus Batriscenellus Jeannel (Staphylinidae, Pselaphinae, Batrisitae) with description of one new species. 2 records from A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae). 13 records from Opheliidae (Annelida: Polychaeta) from the western Pacific islands, including five new species. 234 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 4 records from Deep-sea Cirripedia Thoracica (Crustacea) from the northeastern Atlantic collected by French expeditions. 2 records from A new species of Curculionichthys (Siluriformes: Loricariidae) from the north edge of the Brazilian Shield, lower Amazon basin. 4 records from Taxonomic revision of Phascogale tapoatafa (Meyer, 1793) (Dasyuridae; Marsupialia), including descriptions of two new subspecies and confirmation of P. pirata Thomas, 1904 as a ‘ Top End’ endemic. 5 records from New species of Tomocerus (Entomobryomorpha, Tomoceridae) with remarkable form of mucronal dorsal lamella. 6 records from New Neotropical species of Lachesilla Westwood, in species group forcepeta (Psocodea: ‘ Psocoptera’: Lachesillidae). 21 records from Entomobrya (Collembola, Entomobryidae) for the Canary Islands. 2 records from A new species of the genus Phymorhynchus (Neogastropoda: Raphitomidae) from a hydrothermal vent in the Manus Back-Arc Basin. 32 records from A taxonomic monograph of the genus Solariola Flach, 1908 (Coleoptera: Curculionidae: Entiminae). 5 records from Gamelia bennetti sp. nov., a new Saturniidae species from Trinidad and Tobago (Lepidoptera: Bombycoidea). 3 records from Two new species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with a new record from Australia. 9 records from Description of new species of algal-boring Limnoria (Crustacea, Isopoda, Limnoriidae) from Japan and redescription of Limnoria segnoides Menzies, 1957 and L. nagatai Nunomura, 2012. 86 records from The genus Haplodrassus Chamberlin, 1922 in the Mediterranean and the Maghreb in particular (Araneae: Gnaphosidae). 12 records from Five new species of Spartaeus Thorell, 1891 from China (Araneae: Salticidae). 6 records from Provisional checklist of the Tettigonioidea (Insecta: Orthoptera) from São Tomé & Príncipe with taxonomic remarks, bioacoustical data and the description of new taxa. 214 records from Museo de Historia Natural Universidad de Caldas - Colección de Vertebrados e Invertebrados - Lepidoptera. 198 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 1 records from A new genus and species of axiid shrimp (Crustacea, Decapoda) from a southwestern Indian Ocean seamount. 1 records from Remarkable new Australian mothflies (Diptera, Psychodidae). 4565 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla (Guerrero). 22048 records from MBML Herbarium - Museu de Biologia Mello Leitão - Herbário Virtual Reflora. 141 records from Peracarida of Bernardo O’Higgins National Park (S Chile). 1 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 1 records from A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 274018 records from R. L. McGregor Herbarium Vascular Plants Collection. 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 2024 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 4 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 3 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 15 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 498 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 3986 records from FBIP: What are the impacts of global climate change on arid soil microbial communities?. 6 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 3 records from Universidad de San Carlos de Guatemala - Colección de Porifera. 2 records from Three new species of the barracudina genus Lestidium (Aulopiformes: Paralepididae) from the Indo-West Pacific. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 7 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 7 records from A revision of African helmeted terrapins (Testudines: Pelomedusidae: Pelomedusa), with descriptions of six new species. 22 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from New cave-dwelling Plakina (Plakinidae, Homoscleromorpha, Porifera) from Martinique Island (French Antilles). 2 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 310516 records from CAS Herpetology (HERP). 8 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 1 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 39 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 3 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 3627 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 23 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Reptiles). 870 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 6 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 4 records from Le genre Argentina Hill (Rosaceae) en Nouvelle-Guinée: une espèce et une combinaison nouvelles. 282 records from Middlebury College Bee Collection. 8 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13509 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 6827 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT (Plantas). 3 records from Two new species of flavomaculata-group of the genus Macrophya Dahlbom (Hymenoptera: Tenthredinidae) from China. 160 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 10560 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 35 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 1571 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 1 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 1218 records from UTEP Herpetology Osteology (Arctos). 24 records from Three new species of Ochyrocera (Araneae, Ochyroceratidae) from Southeastern Brazil. 1 records from Review of the effusus group of the Lanternfly genus Pyrops Spinola, 1839, with one new species and notes on trophobiosis (Hemiptera: Fulgoromorpha: Fulgoridae). 3 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 2 records from Description of a new species of Chrysina Kirby (Coleoptera: Scarabaeidae: Rutelinae) from the Sierra Azul, Oaxaca, Mexico, a new synonymy, and notes on Chrysina species found in the Sierra Azul. 26 records from Dendrochirotida (Echinodermata: Holothuroidea) from the northeastern coast of Brazil. 11962 records from Museu Paraense Emílio Goeldi - Diptera Collection. 2 records from A new Occidozyga from Sarawak, Malaysian Borneo (Anura: Dicroglossidae). 6 records from A new forest dwelling button spider from South Africa (Araneae, Theridiidae, Latrodectus). 54284 records from Herbarium Senckenbergianum (FR). 49506 records from Invertebrate Zoology Division, Yale Peabody Museum. 12 records from Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records. 119 records from Colección de Gusanos Cinta (Nemertea) de la región de Santa Marta. 31 records from New Species And New Records Of Plecoptera From Korea And The Russian Far East. 4 records from Three new species Willowsia (Collembola: Entomobryidae) from China and notes on W. japonica. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 4 records from Nymphs of some Nearctic leafhoppers (Homoptera, Cicadellidae) with description of a new tribe. 1 records from The advertisement call of Leptobrachella liui Fei and Ye, 1990 (Anura: Megophryidae). 87807 records from CHSC - CSU Chico, Chico State Herbarium - Vascular Plants. 48524 records from Swiss National Vespoidea Databank. 20 records from CHAS Ichthyology Collection (Arctos). 2 records from First record of the cimicomorphan family Plokiophilidae (Hemiptera, Heteroptera) from China, with description of a new species of Plokiophiloides. 15 records from New Species of Australian Lestidae (Odonata). 10 records from New Species And Records Of Asian Peltoperlidae (Insecta: Plecoptera). 19 records from Colección de muestras biológicas del Centro Oceanográfico de Canarias. 34 records from Sipuncula collection of National Museum of Nature and Science. 50 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species. 8 records from Neofidia Strother, a new name for Fidia Baly, 1863 and redescription of Fidia kanaraensis (Jacoby, 1895) with a new host record and notes on natural history (Coleoptera, Chrysomelidae, Eumolpinae). 922 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 11469 records from Catálogo de insectos de la colección del Centro de Entomología. 2241 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 5 records from Luciobarbus lanigarensis and L. numidiensis, two new species of barbels from the Mediterranean Sea basin in North Africa (Teostei: Cyprinidae). 753 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 6 records from Two new species of eyeless amphipods from a coastal area in Japan (Crustacea: Amphipoda: Hadziidae, Melitidae), with reinstatement of the genus Paraniphargus Tattersall, 1925. 1 records from Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky. 24 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 6 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 11031 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 7 records from Gastrointestinal nematodes of Paramelomys levipes and P. mollis (Rodentia Muridae) from Papua, Indonesia and Papua New Guinea with the descriptions of three new genera and nine new species (Nematoda). 84 records from DAYO: Invasive Alien Reptiles in the Philippines. 3 records from Description of five new species of Epitola sensu lato (Lepidoptera: Lycaenidae Poritiinae) from West and Central Africa. 3 records from Two new species of Styela (Tunicata: Ascidiacea) from the tropical West Atlantic Ocean. 235 records from New state records for Coniopterygidae (Neuroptera) with an updated list of species in North America north of Mexico. 242 records from MPM Herpetology. 11 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 70288 records from Fairchild Tropical Botanic Garden (FTG). 10 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 691 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 2 records from The Vietnamese population of Megophrys kuatunensis (Amphibia: Megophryidae) represents a new species of Asian horned frog from Vietnam and southern China. 1 records from A new species of the genus Mallomonas (Synurophyceae), Mallomonas spinosa sp. nov., from Vietnam. 116937 records from Australian National Wildlife Collection provider for OZCAM. 20388 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 2829 records from HUSC - Herbário Unisanta. 1 records from A new genus, Protaustrosimulium, for four species of Australian black flies (Diptera: Simuliidae). 34 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 7265 records from NHM, Heteroptera. 75124 records from Algae, Norwegian College of Fishery Science. 2 records from Mugilogobius hitam, a new species of freshwater goby (Teleostei: Gobioidei: Gobiidae) from Lake Towuti, central Sulawesi, Indonesia. 7 records from Asian cave-adapted diplurans, with the description of two new genera and four new species (Arthropoda, Hexapoda, Entognatha). 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1054 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 1 records from A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan. 1 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 4 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 1506521 records from Australian Museum provider for OZCAM. 136 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 4 records from A new genus of Pulaeini (Acari: Prostigmata: Cunaxidae) from South-East Asia. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 49 records from iran-marine-ray-finnedfishes-1963-70. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 13 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 1 records from Characidium chancoense, a new species of South American darter from the Río Cauca drainage, Colombia (Characiformes: Crenuchidae). 8 records from Moenkhausia rubra, a new species from rio Juruena, upper rio Tapajós basin, Brazil (Characiformes: Characidae). 7 records from Cytheroid ostracods (Crustacea) from South Korea, with description of a new species. 180 records from osac_oarisma. 140249 records from Vascular plant herbarium, UiT Tromsø Museum. 1 records from Minjerribah (Diptera: Dolichopodidae), a new genus from coastal Queensland, Australia. 25 records from Terre d'huiles. 27 records from Gryon ancinla Kozlov & Lê (Hymenopt
Keywords: GBIF; biodiversity; species occurrences